PENGARUH KUALITAS PRODUK, HARGA, DAN KEPERCAYAAN TERHADAP KEPUTUSAN PEMBELIAN PADA TOKO A3 PARFUM UNGARAN TIMUR - Yeni Dwi Indriani; Ninik Dwi Atmini; Adji Seputro (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) - Institut Teknologi dan Bisnis (ITB) Semarang, 2024)
The aims of this research: 1). Know and explain the influence of product quality on purchasing decisions at the A3 Parfum Ungaran Timur store 2). Understand and explain the influence of price on purchasing decisions at the A3 Parfum Ungaran Timur shop 3). Understand and explain the influence of trust on purchasing decisions at the A3 Parfum Ungaran Timur store. The population in this study were all consumers who bought perfume at the A3 Perfume Ungaran Timur Shop. This research was carried out using an accidental sampling technique, obtaining a sample of 96 respondents. The analysis technique used is multiple linear regression. The research results can be concluded that: 1). Product quality has a positive and significant effect on purchasing decisions, 2) Price has a positive and significant effect on purchasing decisions, 3) Trust has a positive and significant effect on purchasing decisions.